Kramers doublets, phonons, crystal-field excitations, and their coupling in Nd_{2}ZnIrO_{6} - Birender Singh; M. Vogl; S. Wurmehl; S. Aswartham; B. Büchner; Pradeep Kumar (Physical Review Research, 2020)
We report comprehensive Raman-scattering measurements on a single crystal of double-perovskite Nd_{2}ZnIrO_{6} in a temperature range of 4–330 K, spanning a broad spectral range from 20 to 5500cm^{−1}. The paper focuses on lattice vibrations and electronic transitions involving Kramers doublets of the rare-earth Nd^{3+} ion with local C_{1} site symmetry. Temperature evolution of these quasiparticle excitations has allowed us to ascertain the intricate coupling between lattice and electronic degrees of freedom in Nd_{2}ZnIrO_{6}. Strong coupling between phonons and crystal-field excitation is observed via renormalization of the self-energy parameter of the phonons, i.e., peak frequency and linewidth. The phonon frequency shows abrupt hardening and linewidth narrowing below ∼100 K for the majority of the observed first-order phonons. We observed splitting of the lowest Kramers doublets of ground state (^{4}I_{9/2}) multiplets, i.e., lifting of the Kramers degeneracy, prominently at low temperature (below ∼100 K), attributed to the Nd-Nd/Ir exchange interactions and the intricate coupling with the lattice degrees of freedom. The observed splitting is of the order of ∼2–3 meV and is consistent with the estimated value. We also observed a large number of high-energy modes, 46 in total, attributed to the intraconfigurational transitions between 4f^{3} levels of Nd^{3+} coupled to the phonons reflected in their anomalous temperature evolution.